The Development of Science in the Digital Era and Its Influence on Islamic Culture - Dadang Abdau, Asep (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2023)
The development of science in the digital era has had a significant impact on Islamic culture. In this era, the dissemination and access of information has become faster and wider, enabling Muslims throughout the world to interact and share knowledge. Digital technology has facilitated the spread of Islamic teachings through various platforms, such as social media, mobile applications and websites. However, this development also brings challenges. For example, false or misleading information about Islam can easily spread, and this can affect Muslims' religious understanding and practices. Apart from that, the digital era can also influence Islamic cultural values and traditions, because Muslims are increasingly exposed to various other cultures and lifestyles via the internet. However, the digital era also opens up new opportunities for the development of Islamic science and culture. For example, digital technology can be used to preserve and promote Islamic art and culture, such as calligraphy and music. Apart from that, digital platforms can also be used for Islamic education, such as online Al-Qur'an learning. Overall, the development of science in the digital era has a complex and diverse influence on Islamic culture. Therefore, it is important for Muslims to understand and navigate these changes wisely.